2018
DOI: 10.3389/fpsyt.2018.00635
|View full text |Cite
|
Sign up to set email alerts
|

A 16-Year Cohort Analysis of Autism Spectrum Disorder-Associated Morbidity in a Pediatric Population

Abstract: Introduction: This chapter presents the analysis of physician-diagnosed International Classification of Diseases (ICD version 9) disorders and diseases associated with autism spectrum disorders (ASD) in a 16-year pediatric cohort.Materials and Methods: The sample (n = 47,180; 62% male) consisted of children in the Alberta Health Services Calgary Health Region catchment under the age of 3 years, who received any physician-assigned ICD 9 diagnosis before the age of three between April 1993 and December 31, 1994.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…We included 56 studies that reported the mean and/or median age at ASD diagnosis, of which 46 reported an overall ASD mean age at diagnosis between 30.9 and 574.4 months (Becerra-Culqui et al, 2018; Begeer et al, 2013; Bello-Mojeed et al, 2017; Bent et al, 2015; Berg et al, 2018; Bravo Oro et al, 2012; Brett et al, 2016; Carias & Wevrick, 2019; Cawthorpe, 2018; Crane et al, 2016; Daniels et al, 2017; Darcy-Mahoney et al, 2016; Emerson et al, 2016; Garrido et al, 2018; Goodwin et al, 2017; Hagberg & Jick, 2017; Hall-Lande et al, 2018; Hausman-Kedem et al, 2018; Höfer et al, 2019; Hrdlicka et al, 2016; Jo et al, 2015; Kentrou et al, 2019; Kurasawa et al, 2018; Lagunju et al, 2014; Larsen, 2015; Lo et al, 2017; Magaña et al, 2013; Manohar et al, 2019; Martinez et al, 2018; Masri et al, 2013; May et al, 2017; Mazurek et al, 2014; Miodovnik et al, 2015; Mishaal et al, 2014; Mpaka et al, 2016; Ribeiro et al, 2017; Rutherford et al, 2016; Salomone et al, 2016; Sheldrick et al, 2017; Shrestha et al, 2019; Sicherman et al, 2017; Talero-Gutiérrez et al, 2012; Ververi et al, 2012; Wei et al, 2018; Zablotsky et al, 2018). Of the 56 studies, 24 reported an overall ASD median age at diagnosis (only or combined with mean age at diagnosis score) between 28 and 96 months (Baio et al, 2018; Becerra-Culqui et al, 2018; Bent et al, 2015;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 56 studies that reported the mean and/or median age at ASD diagnosis, of which 46 reported an overall ASD mean age at diagnosis between 30.9 and 574.4 months (Becerra-Culqui et al, 2018; Begeer et al, 2013; Bello-Mojeed et al, 2017; Bent et al, 2015; Berg et al, 2018; Bravo Oro et al, 2012; Brett et al, 2016; Carias & Wevrick, 2019; Cawthorpe, 2018; Crane et al, 2016; Daniels et al, 2017; Darcy-Mahoney et al, 2016; Emerson et al, 2016; Garrido et al, 2018; Goodwin et al, 2017; Hagberg & Jick, 2017; Hall-Lande et al, 2018; Hausman-Kedem et al, 2018; Höfer et al, 2019; Hrdlicka et al, 2016; Jo et al, 2015; Kentrou et al, 2019; Kurasawa et al, 2018; Lagunju et al, 2014; Larsen, 2015; Lo et al, 2017; Magaña et al, 2013; Manohar et al, 2019; Martinez et al, 2018; Masri et al, 2013; May et al, 2017; Mazurek et al, 2014; Miodovnik et al, 2015; Mishaal et al, 2014; Mpaka et al, 2016; Ribeiro et al, 2017; Rutherford et al, 2016; Salomone et al, 2016; Sheldrick et al, 2017; Shrestha et al, 2019; Sicherman et al, 2017; Talero-Gutiérrez et al, 2012; Ververi et al, 2012; Wei et al, 2018; Zablotsky et al, 2018). Of the 56 studies, 24 reported an overall ASD median age at diagnosis (only or combined with mean age at diagnosis score) between 28 and 96 months (Baio et al, 2018; Becerra-Culqui et al, 2018; Bent et al, 2015;…”
Section: Resultsmentioning
confidence: 99%
“…We excluded eight of 45 papers reporting the mean age at diagnosis from the meta-analysis: six because no SD was reported (Bravo Oro et al, 2012; Goodwin et al, 2017; Hagberg & Jick, 2017; Jo et al, 2015; Masri et al, 2013; Sheldrick et al, 2017) and two because no sample size for the ASD population was given (Crane et al, 2016; May et al, 2017). Total sample sizes and SDs were calculated from three studies that reported the age at diagnosis by age group (Begeer et al, 2013; Rutherford et al, 2016) or gender (Cawthorpe, 2018) but not for the entire sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidities may be psychiatric [6], neurological [7], or related to medical conditions beyond the brain in the field of Pediatrics or General Medicine [8]. Recent literature has demonstrated that people with ASD diagnosis may have multiple comorbidities in different combinations and severity [9] and even temporal, transient hyper-multimorbidity. Multimorbidity is present when multiple medical issues (called comorbidities) are diagnosed in the same person.…”
Section: Introduction-the Backgroundmentioning
confidence: 99%
“…Absent from this body of work has been the prospective study of the multi-morbidity associated with early dental caries. Multi-morbidity is an emerging field in the management of disease in terms of understanding its etiology, sequelae, and potential mechanisms, notwithstanding the relationship of early dental caries to the preventable burden of disease [9,[29][30][31][32][33]. To date examination of the relationship of epidemiological investigation to mechanism pertaining to early dental caries has not included study of multi-morbidity [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%